Queensland nursing staffs' perceptions of the preparation for practice of registered and enrolled nurses - Hegney, Desley; Eley, R.; Francis, K. (Churchill Livingstone, 2013)
Introduction: In Australia, unlike other countries, programmes which lead to registration as a registered or enrolled nurse (called “entry to practice” programmes) are carried out solely in the tertiary sector. In Australian nursing and the wider community, there continues to be a debate over the place of preparation and the “work readiness” of graduates. Background: Despite several opinion papers on the preparation of registered nurses, there is a dearth of published research on the perceptions of the clinical nursing workforce on the suitability of the current preparation for practice models. Methods: Data were collected from approximately 3000 nurses in Queensland, Australia in 2007 and 2010. The aim of these studies was to ascertain issues around nursing work. This paper reports on qualitative data that were collected as part of that larger survey. Specifically this paper provides the thematic analysis of one open-ended question: “what are the five key issues and strategies that you see could improve nursing and nursing work?” as it was apparent when we undertook thematic analysis of this question that there was a major theme around the preparation of nurses for the nursing workforce. We therefore carried out a more detailed thematic analysis around this major theme.Results: The major sub-themes that we identified from comments on the preparation of the nursing workforce were: perceptions of lack of clinical exposure and the need to increase the amount of clinical hours; the design of the curriculum, the place of preparation (solely within industry or a great focus on industry), financial consideration (students to be paid for their work); and in 2007 only, the need for students to have better time management. Discussion: The findings suggest that a majority of respondents believed there should be changes to the entry to practice preparation for nurses. The major focus of these comments was the perception of insufficient clinical experience and inappropriate curriculum content. Thus, graduates are not “work ready”. Conclusion: The attitude of clinical nurses, who work closely with student nurses, influences the workplace experience of student nurses. It is apparent from the statements of respondents in this study, that there is a need for stronger industry/academic partnerships, particularly around the design and implementation of the entry-to-practice curriculum.